Addressing local health service problems through integrated governance: a case study from Senegal. Issue 3 (3rd April 2023) - Wetterberg, Anna; Frazer, Sarah; Johnson, Eric
ABSTRACT: Local governments, facility staff, and civil society actors are often best placed to identify and address local service delivery problems. We explore how an integrated governance approach – that empowers local actors and promotes cross-sectoral collaboration – affected health service problem-solving in Senegal. Using a quasi-experimental design, we draw on survey data to trace how local health governance bodies address problems. Findings suggest an integrated governance approach improves health service readiness through increased citizen involvement and greater access to resources. These exploratory findings illuminate a growing literature linking initiatives that empower local governments, citizen groups, and multi-stakeholder governance bodies to meaningful service improvements.